Nervous form of ketosis in cows and its treatment - Sudhakara Reddy, B; Reddy, B. Soma Sekhar; Reddy, Y. V. Pridhvidhar; Vennkatasivakumar, R. (International Journal of Biological Research, 2014)
Ketosis is defined as an abnormal rise of the ketone or acetone bodies in the body. The ketone bodies are organic chemical compounds and include acetone, acetoacetic acid, and beta hydroxy butyric acid. Present study reports the primary nervous ketosis in three cows at their peak milk yield. Cows exhibited the bellowing, head pressing and reluctance to take concentrates. Low serum glucose, high levels of blood urea nitrogen with ketonuria was observed. Cows showed fruitful recovery after treatment with 25% glucose solution, dexamethasone and glycerin along with supportive therapy. Keywords: Cows, Dextrose, Ketosis, Nervous Signs.